Analisis Produktivitas Waktu dan Perbandingan Biaya Pekerjaan Tiang Pancang - Prabowo, Yudi Setio; Pratama, Andika; Putra, Al Fiillian Sah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The advancement of technology continues to progress to meet society's need for efficiency and convenience in work, including improving time productivity in structural tasks such as pile foundation installation in construction projects. This research aims to analyze time efficiency and compare the field Budget Plan (RAB) costs with the SNI 2022 Budget Plan (RAB) costs for pile foundation installation. The study was conducted using unstructured interview methods with the site manager to gather primary data from the construction project of PT. Gudang Garam Tbk's cigarette depot building. A quantitative method was applied in this research.The analysis revealed that for the installation of 152 pile units, the highest time productivity was recorded at 0.384 m/min or 23,07 m/hour, the lowest at 0.192 m/min or 11,51 m/hour, and an average installation rate of 0.282 m/min or 16,95 m/hour. Additionally, this study also obtained a comparison between the field RAB (Budget Plan) costs and the SNI 2022 RAB costs. The field RAB cost for pile installation was Rp287,280,000,-. Meanwhile, the SNI 2022 RAB cost for pile installation was Rp441,663,676,-.